Oxytocin signaling in the medial amygdala is required for sex discrimination of social cues - Shenqin Yao; Joseph Bergan; Anne Lanjuin; Catherine Dulac (eLife, 2017)
The neural control of social behaviors in rodents requires the encoding of pheromonal cues by the vomeronasal system. Here we show that the typical preference of male mice for females is eliminated in mutants lacking oxytocin, a neuropeptide modulating social behaviors in many species. Ablation of the oxytocin receptor in aromatase-expressing neurons of the medial amygdala (MeA) fully recapitulates the elimination of female preference in males. Further, single-unit recording in the MeA uncovered significant changes in the sensory representation of conspecific cues in the absence of oxytocin signaling. Finally, acute manipulation of oxytocin signaling in adults is sufficient to alter social interaction preferences in males as well as responses of MeA neurons to chemosensory cues. These results uncover the critical role of oxytocin signaling in a molecularly defined neuronal population in order to modulate the behavioral and physiological responses of male mice to females on a moment-to-moment basis.